Know your fans using word-of-mouth marketing to sell your products - Libert, Barry (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from We are smarter than me: How to unleash the power of crowds in your business (ISBN: 9780132244794) by Barry Libert and Jon Spector. Put crowdsource marketing to work--and magnify the impact of your marketing efforts with the authenticity and power of real customers!"--Resource description page.
Keywords: Word-of-mouth advertising; Strategic alliances (Business); Social participation -- Economic aspects; Viral marketing; Customer relations; Customer services; Bouche-à-oreille (Publicité); Alliances stratégiques (Affaires); Participation sociale; Aspect économique; Marketing viral; Service à la clientèle